Compendium data and preliminary results based on alum sludge and gravel continuous fixed-packed-bed column substrate as sustainable practice for constructed wetland development in northern Egypt. Issue 1 (1st August 2022) - Tony, Maha A.
Abstract: The present investigation represents the valuable reclaims of the aluminum-based waterworks sludge that is so called "alum sludge" to close the loop concerning the sludge waste production and the sustainable ecosystem. In this study the adsorption behaviors of aluminium based sludge, namely alum sludge (AS) and gravel as cost-efficient adsorbents regarding dye elimination from aqueous synthetic stream were analyzed in fixed bed column. The influence of variable boundaries such as column pack depth and influent concentration on the effluent concentrations via breakthrough curves were examined. It is estimated that the removal uptake and sorption capabilities elevated as the initial influent loading of the dye dismissed for the fixed bed height of the both adsorbents, namely, gravel and AS. Thereafter, a preliminarily results were checked to investigate the feasibility of the adsorption column in Reactive Blue 4 (RB4) adsorption. The maximum adsorption capacities were observed around 4 mg L-1 for sample with pH 7.5 that is signified as the natural pH of the synthetic stream. However, increasing the initial dye loading increasing the adsorption capacity which reached to 5.5 mg L-1 for the dye loading 27.8 mg L-1 of Reactive Blue 4 (RB4). Thus, the first results will be a valued scheme in the development of adsorption systems to build up a constructed wetland facility.